Higher Education Research and Reality: They Need to Be Better Aligned - Zha, Qiang (International Higher Education, 2024)
This article argues that there are currently gaps existing between higher education research and reality. Such a segregation indicates a kind of misalignment and disjuncture between the two realms, and calls for reimagining and transforming the field of higher education research.